2022
DOI: 10.21203/rs.3.rs-1915834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term Cardiovascular Outcomes of Multisystem Inflammatory Syndrome in Children Associated with COVID-19 using an Institution Based Algorithm

Abstract: Background: Cardiovascular involvement is a major cause of inpatient and intensive care unit morbidity related to Multisystem inflammatory syndrome in children (MIS-C). The objective of this study was to identify long-term cardiovascular manifestations of MIS-C. Methods: We included 80 consecutive patients admitted to the intensive care unit with MIS-C who were evaluated for a year in our follow-up clinic using an institution protocol. The outcome measures were cardiac biomarkers (troponin and BNP), electrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In survivors, most people recovered, and some patients showed long-term symptoms, commonly referred to Post-Covid Syndromes [39,40] . Numerous studies have shown that the risk of cardiovascular disease, including heart attack and stroke, increased signi cantly over a long period of time after the patients infected with Omicron BF.7, these symptoms can cause myocarditis, heart attack, cardiac arrest and sudden death and so on [41][42][43][44] . The patients could include outpatients and asymptomatic patients under the age of 50.…”
Section: Abnormal Kidney Function In Patients Infected Omicron Bf7mentioning
confidence: 99%
“…In survivors, most people recovered, and some patients showed long-term symptoms, commonly referred to Post-Covid Syndromes [39,40] . Numerous studies have shown that the risk of cardiovascular disease, including heart attack and stroke, increased signi cantly over a long period of time after the patients infected with Omicron BF.7, these symptoms can cause myocarditis, heart attack, cardiac arrest and sudden death and so on [41][42][43][44] . The patients could include outpatients and asymptomatic patients under the age of 50.…”
Section: Abnormal Kidney Function In Patients Infected Omicron Bf7mentioning
confidence: 99%
“…Data on secondary damage to the cardiovascular system varies depending on the utilized techniques, parameters, and follow-up period. Results range from complete remission to 36% measurable long-term damage (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple pioneering efforts have investigated symptoms of long COVID for hospitalized individuals, representing the minority of people with COVID-19 [5]- [7]. An extensive patient-led survey has been conducted in an outpatient setting to explore the symptoms of long COVID over seven months [3].…”
Section: Introductionmentioning
confidence: 99%